Evaluation of MALDI-TOF Mass Spectrometry and Sepsityper Kit™ for the Direct Identification of Organisms from Sterile Body Fluids in a Canadian Pediatric Hospital - Manal Tadros; Astrid Petrich (Canadian Journal of Infectious Diseases and Medical Microbiology)
Matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) can be used to identify bacteria directly from positive blood and sterile fluid cultures. The authors evaluated a commercially available kit – the Sepsityper Kit (Bruker Daltonik, Germany) – and MALDI-TOF MS for the rapid identification of organisms from 80 flagged positive blood culture broths, of which 73 (91.2%) were blood culture specimens and seven (8.7%) were cerebrospinal fluid specimens, in comparison with conventional identification methods. Correct identification to the genus and species levels was obtained in 75 of 80 (93.8%) and 39 of 50 (78%) blood culture broths, respectively. Applying the blood culture analysis module, a newly developed software tool, improved the species identification of Gram-negative organisms from 94.7% to 100% and of Gram-positive organisms from 66.7% to 70%.